A comparative study of cumulative stress patterns within 14 days postpartum in healthy mothers and those with gestational diabetes: A prospective study. Issue 41 (15th October 2021) - Park, Seungmi; Yu, Soo-Young; Kwak, Eunju; Min, Deulle
Abstract : Abstract: Although the number of mothers with gestational diabetes mellitus (GDM) is on the rise, only few studies have examined the cumulative stress associated with breastfeeding after childbirth. GDM mothers are susceptible to stress due to insulin resistance, and their level of stress is associated with breastfeeding. This study aimed to identify patterns of stress change over time in GDM mothers and healthy mothers and to identify the factors influencing those patterns. The participants of this study were mothers within 14 days after childbirth. The GDM group consisted of 32 mothers, and the healthy group comprised 30 mothers. Cumulative stress was measured in terms of heart rate variability, and linear mixed models were used to analyze changes over time. The cumulative stress of healthy mothers was about 8 points higher than that of mothers with GDM (t = −2.95, P  = .005). The cumulative stress level was inversely associated with the mother's age (β=-1.20, P  = .018), the mother's weight (β=-0.64, P  = .008), and the baby's body mass index (β=-3.09, P  = .038). Furthermore, an insufficient amount of breast milk was associated with higher stress (β=16.09, P  = .007). GDM mothers and healthy mothers experienced different patterns of cumulative stress. Breastfeeding should be started quickly to promote health and stress reduction among mothers who are physically and psychologically vulnerable after childbirth. It is necessary to incorporate programs to promote breastfeeding considering stress levels at an appropriate time according to the mother's health condition.